Mechanical Properties, Biocompatibility, and Environmental Impact of Direct Printed Orthodontic Aligners - A Literature Review - Ortner, Nikola Sophie (Archive of Orofacial Data Science, 2025)
AIM: The aim of this study was to perform a systematic review of the orthodontic literature regarding the mechanical properties of thermoformed aligners in comparison to direct printed aligners. METHODS: This study searched German and English publications in PubMed and Scopus using Boolean operators to find articles on 3D-printed and thermoformed aligners, focusing on mechanical properties, biocompatibility, and environmental impacts. The search was limited to articles from the past 10 years. Publication types such as systematic reviews, comments, and conference abstracts were excluded. RESULTS: A total of 606 potentially relevant studies were identified, of which 16 were included in the investigation after applying selection criteria based on the PICO research approach. Directly printed aligners demonstrated several advantages in biocompatibility, mechanical properties, and environmental impact. However, some studies indicated adverse effects of resin aligners, attributed to variations in the manufacturing process. CONCLUSION: Within the limitations of this study, it was determined that three-dimensional printing technology offers numerous high-quality benefits compared to conventional thermoforming. The mechanical properties of 3D printed materials are influenced by the printing and post-processing methods, as well as the different 3D printers employed, leading to expected variations in their therapeutic effectiveness.